2021
DOI: 10.1021/acs.inorgchem.1c00301
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and Magnesium Bis(β-diketiminate) Complexes: Impact of the Alkylene Bridge on Schlenk-Type Rearrangements

Abstract: Dinuclear heteroleptic alkaline-earth-metal complexes are interesting synthetic targets because the close proximity of two metals allows for cooperative effects. However, these complexes are also prone to undergoing Schlenk-type rearrangements, affording less-active homoleptic complexes. Here we present the metalation of bis­(β-diketimine) ligands possessing flexible bridging groups, i.e., 1,2-ethylene, 1,3-propylene, and trans-1,2-cyclohexylene, using calcium and magnesium precursors. Four mononuclear homolep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 140 publications
0
6
0
Order By: Relevance
“…Single crystal X-ray analysis revealed these to be the charge-separated complex [Mg·6THF] 2+ 2[AlPh 4 ] − ( 1a , Fig. 1) which we believe is a minor Schlenk equilibrium 13 product of the targeted complex 1 . However, its anionic moiety unequivocally confirms that ligand (phenyl) transfer from Mg to Al has occurred as intended, supporting the 27 Al NMR observations.…”
Section: Resultsmentioning
confidence: 95%
“…Single crystal X-ray analysis revealed these to be the charge-separated complex [Mg·6THF] 2+ 2[AlPh 4 ] − ( 1a , Fig. 1) which we believe is a minor Schlenk equilibrium 13 product of the targeted complex 1 . However, its anionic moiety unequivocally confirms that ligand (phenyl) transfer from Mg to Al has occurred as intended, supporting the 27 Al NMR observations.…”
Section: Resultsmentioning
confidence: 95%
“…However, monitoring the reaction of I Na with CaI 2 by NMR spectroscopy it was observed that two species are present in solution (see ESI,† Section S3). The same product mixture was also generated when reacting isolated 2 at room temperature with an excess of CaI 2 indicating that 2 is participating in a kind of Schlenk equilibrium 9 (see Scheme 2). Indeed the minor product was identified as 2 while for the main product a composition of [CaI(THF) 4 (L t Bu NiCO 2 )], 2′ , is suggested (see below).…”
mentioning
confidence: 85%
“…While bis(β-diketiminate) calcium-hydride complexes have not yet been reported, the Harder group was able to access dimeric tetranuclear C but also a larger octanuclear magnesium-hydride cluster. The absence of the former so far is most likely due to the pronounced tendency of calcium to undergo Schlenk-type rearrangements associated with the formation of homoleptic complexes, which is even more pronounced in the case of ditopic ligands because of entropic effects …”
Section: Introductionmentioning
confidence: 99%
“…Later on, it was shown that mononuclear three-coordinate magnesium-hydride complexes are also stable without an additional coligand, i.e., when using a sterically demanding β-diketiminate . Besides the utilization of β-diketimines, ditopic bis­(β-diketimine)­s have also been applied in alkaline-earth metal chemistry . While bis­(β-diketiminate) calcium-hydride complexes have not yet been reported, the Harder group was able to access dimeric tetranuclear C but also a larger octanuclear magnesium-hydride cluster.…”
Section: Introductionmentioning
confidence: 99%